The Development of Islamic Civilization in the World: Knowledge, Integration and Innovation (750-1258 CE) - Thohir, Ajid; Septiadi, Muhammad Andi (Journal of Al-Tamaddun, 2025)
The rise of Islamic civilization marked a significant transformation in global history, replacing the dominance of the Persian and Roman Empires with an extensive rule spanning half of Asia, Africa, and parts of Europe in a remarkably short period. This study employs historical research methods structured through four critical steps: heuristics, criticism, interpretation, and historiography. It aims to explore the interconnected processes of conquest, cultural assimilation, and the flourishing of knowledge by analysing the key mechanisms and sociopolitical factors that facilitated these developments. Unlike previous studies, this research highlights the direct impact of cultural assimilation on scientific, technological, and economic advancements in Islamic civilization. Specifically, it investigates how the integration of local traditions with Islamic principles contributed to the development of algebra, medicine, optics, engineering, and economic models, many of which laid the foundation for modern disciplines. Additionally, this study highlights the pivotal role of Islamic history as a catalyst for innovation, demonstrating how early Islamic societies developed sophisticated trade networks, advanced industrial production methods, and innovative financial institutions that significantly influenced global economic structures. By providing new insights into the mechanisms through which Islamic civilization absorbed and enhanced existing knowledge systems, this research contributes to a deeper understanding of its enduring legacy in shaping modern scientific and economic thought.